Efektivitas Penyampaian Konten Edukasi Agrowisata terhadap Pemahaman Wisatawan di Merapi Farma Herbal Farm Sleman - Nuryuda Irdana; Rina Widiastuti; Wiku Purwono (Jurnal Pariwisata Terapan, 2021)
During the COVID-19 pandemic, herbal agro-tourism became very popular in Indonesia. Agrotourism is closely related to edu-tourism. To build an edu-tourism business, business actors must apply the concept of creativity so that tourists can gain more useful and educative knowledge. One of the herbal agro-tourism locations in Sleman is Merapi Farma Herbal Farm. Even though educational content, facilities, and completeness of resources in the implementation of agro-tourism packages are already available and well managed, managers still must know whether the implementation of the tour packages run at Merapi Farma Herbal Farm has been effective in delivering educational content to the tourist. This research aimed to determine the types of educational content contained in Merapi Farma Herbal Farm Sleman, and to determine the effectiveness of delivering agro-tourism educational content at Merapi Farma Herbal Farm Sleman to tourists' understanding. The research methods in this study are descriptive method and survey method, and direct observation, interviews with sources, literature studies, and documentation were conducted to find out the types of educational content provided by Merapi Farma Herbal Farm. Meanwhile, to determine the effectiveness of delivering agro-tourism educational content, this research conducted a hypothesis test to tourists/visitors at Merapi Farma Herbal Farm Sleman as the research sample. The tool used to collect data is questionnaires. The analytical tool used to test the hypothesis is the Wilcoxon Test. The results showed that the types of educational content contained at Merapi Farma Herbal Farm Sleman were education about types of herbal plants, how to cultivate herbal plants, the benefits of herbal plants, the history of herbal medicine inIndonesia, and how to mix herbs traditionally. The results of the analysis used the Wilcoxon Test also show that the delivery of agrotourism educational content at Merapi Farma Herbal Farm Sleman can provide tourists with an understanding of herbal plants.